AB1123 SHOULDER PAIN: ARE THERE PREDICTIVE FACTORS OF RESPONSE TO TREATMENT AND OF ULTRASOUND FINDINGS?. (June 2019) - Azevedo, Soraia; Rodrigues, Joana; Faria, Daniela; Neves, Joana; Silva, Joana; Peixoto, Daniela; Alcino, Sérgio; Tavares-Costa, José; Afonso, Carmo; Teixeira, Filipa
Abstract : Background: Shoulder pain is a common cause of consultation in Primary Health Care, and may correspond to up to 30% of the reasons for consultation. Pathology of the rotator cuff is the most common cause of pain. Ultrasound is a valuable diagnostic tool in assessing shoulder disorders; it can be as effective as magnetic resonance imaging. Objectives: To determine the predictive factors of response to treatment and ultrasound findings in shoulder pain. Methods: We performed an analysis of the patients' cases sent to the rheumatology consultation with shoulder pain, every patients had an echography shoulder evaluation, and the rheumatologist decided treatment based on the guidelines for the treatment of shoulder tendinopathies. The use of nonsteroidal anti-inflammatory drug (NSAIDs) and muscle relaxant medications as well as the following techniques: corticosteroids local injection, barbotage, capsular distension and physiotherapy programs were some of the variables assessed. Posteriorly, the patients were clinically assessed in a follow-up visit. Results: A total of 119 patients were evaluated. Men presented a higher risk of distension of the subscapular bursa. There was a statistically significant relationship between the time from the beginning of the symptomatology and treatment response. Diabetes mellitus, arterial hypertension and dyslipidaemia were statistically significantly associated with some rotator cuff lesions and distention of the subscapular bursa. Conclusion: In patients with shoulder pain, early intervention positively influences the response to treatment. Thus, it is important that these patients are evaluated more promptly. Some comorbidities seem to be associated with a higher risk of specific rotator cuff lesions. No relationship was found between response to treatment and age, sex, occupation, previous treatments or type of therapy selected. The associations found in this study seem to have clinical implications. Prevention of rotator cuff disease is a matter of major relevance as well as early institution of treatment. References: [1] Greenberg D.L. 2014 [2] Rechardt M. et al. 2010 [3] Teunis T, et al. 2014 [4] Armstrong A. 2014 [5] Lenza M, et al. 2013 [6] Middelton WD, et al. 2004 [7] Mathias R, et al. 2018 [8] Gatt DL, et al. 2014 [9] Booker S, et al. 2015 [10] Alfahad N, et al. 2015 [11] Le Goff B. et al. 2010 [12] Lansdown DA, et al. 2012 [13] Mantone JK, et al. 2000 [14] Gialanella B, et al. 2013 [15] Titchener AG, et al. 2014 [16] Namdari S, et al. 2014 [17] Boissonnault WG, et al. 2007 [18] Abboud JA, et al. 2010 [19] Lui PPY, et al. 2017 [20] Gumina S, et al. 2013 Disclosure of Interests: None declared